Complex impact of polarized and non-polarized low intense light and methylene blue on growth rate of some opportunistic microorganisms - Pantyo, V. V.; Koval, G. M.; Danko, E. M.; Pantyo, V. I. (Regulatory Mechanisms in Biosystems, 2020)
Resistance to antibiotics is considered as a global and unsolved problem in the branch of medicine. That is why the use of novel non-drug methods of treatment of bacterial and fungal infections is of great relevance. One of such methods is photodynamic treatment, which is a treatment procedure that uses light energy to activate a photosensitizing agent in the presence of oxygen. Due to the broad spectrum of action, the efficacy against antibiotic resistant cells and the lack of selection of photoresistant strains, antimicrobial photodynamic therapy compares favourably with traditional drug therapy, and has emerged in the clinical field as a potential alternative to antibiotics to treat microbial infections. In this article results of studies of the complex effect of methylene blue (0.1% aqueous solution) and LED radiation of the red-infrared spectrum as well as methylene blue and polarized incoherent low-energy radiation (PILER) with a red light filter on the growth rate of some opportunistic microorganisms on solid nutrient media are presented. Standardized suspensions of microorganisms were prepared for research with the subsequent determination of direct impact of polarized and non-polarized radiation (at duration of exposure of 5 min), photosensitizer, and also the set of these factors on growth of the studied microorganisms. The growth intensity of bacteria and yeast-like fungi was determined by the number of their colonies after reseeding on nutrient media in Petri dishes. The obtained data were compared with control groups, which were not influenced by any factors. The results indicate a significant antimicrobial effect of the combined action of different types of radiation and methylene blue on microorganisms, which was manifested in a reduction in the number of colonies by on average 35–45%, compared with the control groups. Comparing the effect of exposure when using LED and PILER light, we have noted its similarity. It is also worth noting a certain antimicrobial activity of 0.1% methylene blue solution on the studied strains, but this was much less pronounced than in the complex effect. The direct effect of both LED and PILER radiation with low duration of exposure caused the stimulation of the growth of the studied microorganisms with an increase in the number of their colonies on Petri dishes by 15–35%. Given the rapid growth of resistance to antimicrobial agents, the described technique can be used as an alternative to traditional antibiotic therapy for the treatment of purulent-inflammatory diseases of the skin and mucous membranes.